Acetazolamide in Decompensated Heart Failure with Volume Overload trial (ADVOR): baseline characteristics. (12th July 2022) - Mullens, Wilfried; Dauw, Jeroen; Martens, Pieter; Meekers, Evelyne; Nijst, Petra; Verbrugge, Frederik H.; Chenot, Fabien; Moubayed, Samer; Dierckx, Riet; Blouard, Philippe; Derthoo, David; Smolders, Walter; et al.
Abstract : Aims: To describe the baseline characteristics of participants in the Acetazolamide in Decompensated Heart Failure with Volume Overload (ADVOR) trial and compare these with other contemporary diuretic trials in acute heart failure (AHF). Methods and results: ADVOR recruited 519 patients with AHF, clinically evident volume overload, elevated N‐terminal pro‐B‐type natriuretic peptide (NT‐proBNP) and maintenance loop diuretic therapy prior to admission. All participants received standardized loop diuretics and were randomized towards once daily intravenous acetazolamide (500 mg) versus placebo, stratified according to study centre and left ventricular ejection fraction (LVEF) (≤40% vs. >40%). The primary endpoint was successful decongestion assessed by a dedicated score indicating no more than trace oedema and no other signs of congestion after three consecutive days of treatment without need for escalating treatment. Mean age was 78 years, 63% were men, mean LVEF was 43%, and median NT‐proBNP 6173 pg/ml. The median clinical congestion score was 4 with an EuroQol‐5 dimensions health utility index of 0.6. Patients with LVEF ≤40% were more often male, had more ischaemic heart disease, higher levels of NT‐proBNP and less atrial fibrillation. Compared with diuretic trials in AHF, patients enrolled in ADVOR were considerably older with higher NT‐proBNP levels, reflecting the real‐world clinical situation. Conclusion: ADVOR is the largest randomized diuretic trial in AHF, investigating acetazolamide to improve decongestion on top of standardized loop diuretics. The elderly enrolled population with poor quality of life provides a good representation of the real‐world AHF population. The pragmatic design will provide novel insights in the diuretic treatment of patients with AHF. Abstract : Baseline characteristics of ADVOR trial participants. ACEi, angiotensin‐converting enzyme inhibitor; AHF, acute heart failure; ARB, angiotensin receptor blocker; IV, intravenous; LVEF, left ventricular ejection fraction; MRA, mineralocorticoid receptor antagonist; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide.